2018
DOI: 10.1371/journal.pone.0191200
|View full text |Cite
|
Sign up to set email alerts
|

When the brain changes its mind: Oscillatory dynamics of conflict processing and response switching in a flanker task during alcohol challenge

Abstract: Despite the subjective experience of being in full and deliberate control of our actions, our daily routines rely on a continuous and interactive engagement of sensory evaluation and response preparation streams. They unfold automatically and unconsciously and are seamlessly integrated with cognitive control which is mobilized by stimuli that evoke ambiguity or response conflict. Methods with high spatio-temporal sensitivity are needed to provide insight into the interplay between automatic and controlled proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 132 publications
(210 reference statements)
7
31
0
Order By: Relevance
“…These are not just different forms of conflict by definition, but also differ in terms of the regions that they have been commonly associated with (right frontal versus frontal midline). Consistent with a previous review of human frontal midline theta from the perspective of rat hippocampal theta (Mitchell et al, 2008), Beaton et al (2018) found that in the flanker task, ventrolateral prefrontal but not frontal midline conflict theta activity, was sensitive to an anxiolytic, alcohol. It therefore appears that there are at least two and possibly more independent conflict mechanisms, and each of these could influence different aspects of anxiety processing.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These are not just different forms of conflict by definition, but also differ in terms of the regions that they have been commonly associated with (right frontal versus frontal midline). Consistent with a previous review of human frontal midline theta from the perspective of rat hippocampal theta (Mitchell et al, 2008), Beaton et al (2018) found that in the flanker task, ventrolateral prefrontal but not frontal midline conflict theta activity, was sensitive to an anxiolytic, alcohol. It therefore appears that there are at least two and possibly more independent conflict mechanisms, and each of these could influence different aspects of anxiety processing.…”
Section: Discussionsupporting
confidence: 86%
“…For example, in addition to right frontal GCSR, theta band activity, albeit from the frontal midline region, has been consistently observed during response- (Cohen, 2014), and outcome-conflict monitoring (Cavanagh and Frank, 2014). Theta band activity has also been observed in the lateral prefrontal regions in the same response-and outcome-conflict monitoring tasks (Nigbur et al, 2012;Tang et al, 2013;Beaton et al, 2018). However, conflict processing is not limited to theta processes.…”
Section: Discussionmentioning
confidence: 97%
“…Theta band activity is important for cognitive control, especially for response inhibition [20][21][22][23][24], and may reflect task-related response selection and control processes [18,25]. Moreover, earlier studies have already demonstrated theta oscillations to be modulated by alcohol [87,88]. Our results therefore suggest that response inhibition is poorer under an acute influence of alcohol due to decreased cognitive control processes [20].…”
Section: Discussionsupporting
confidence: 53%
“…Our results indicate that the oscillatory synchrony within the IFC was dysregulated in BDs and their PLV decrease was associated with alcohol intake (Figure 3). Previous studies reported that alcohol intoxication abolished PLV during a task evoking cognitive control (Beaton et al, 2017;Ehlers et al, 2012).. Altered connectivity in BDs has also been reported during wakeful restingstate as reflected in PLV measured with MEG (Correas et al, 2015). Similarly, resting-state functional connectivity MRI studies in individuals with AUD have found lower connectivity in the executive control (Kim et al, 2017;Müller-Oehring et al, 2015;Weiland et al, 2014) and reward networks (Camchong et al, 2013;Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 85%
“…Early visual activity was assessed in the occipital region (Occ) while the anterior (aIFC) and posterior inferior frontal cortices (pIFC) and sensorimotor cortices (sMOT) were examined bilaterally as shown in Figure 1. Additionally, co-oscillatory interactions between cortical ROIs were estimated by calculating phase-locking values (PLV) between pairs of frontal ROIs in each hemisphere (Figure 3) (Beaton et al, 2017;Lachaux et al, 1999).…”
Section: Megmentioning
confidence: 99%